REDD reckoning: a review of research on a rapidly moving target - Seymour, F. (CAB International, 2012)
This review characterizes the major themes of articles on reducing emissions from deforestation and forest degradation (REDD) published between January 2007 and December 2010 in various peer-reviewed journals, as well as selected reports in the 'grey literature'. The main themes of the articles and reports are analysed in relation to four topics: the global architecture of REDD; measurement and monitoring; national and subnational policies, institutions and governance; and the relationship of REDD to other objectives such as biodiversity conservation, poverty reduction and rights protection. The review identifies a number of topics for further research, including empirical validation of the predicted benefits and risks of implementing REDD policies and projects, and analysis of the degree to which REDD is shaping, or being shaped by, the political economy of forest governance at national and global levels.